The Long-Run Effect of Carbon Emission and Economic Growth in European Countries: A Computational Analysis through Vector Error Correction Model - Sisodia, Gyanendra Singh; Sah, Hemant Kumar; Kratou, Hajer; Mohnot, Rajesh; Ibanez, Alberto; Gupta, Bhumika (International Journal of Energy Economics and Policy, 2023)
The paper seeks to examine the association that exists among a number of energy-related variables such as energy use, renewable energy use, carbon pollutants and the economic growth of European Union countries. The examination of variables focus on twenty-one years of data from 2000 to 2020 using a multidimensional data framework. The findings come from empirical analysis carried out using panel VECM model and associated tests such as, panel unit root test, cointegration and the causality one. The different variables indicated above have positive effects on the growth of economies in various EU member states. Results obtained from the use of the heterogeneous causality test indicated that there is an indirect causality between energy use and the rate at which economies develop. Based on the findings obtained from the study, there is a need for EU member states to establish policies that should help to enhance efficiency in energy use to promote economic development.